Unusual Presentation of Epstein-Barr Virus-Associated Cholestatic Hepatitis in an Infant. Issue 3 (15th August 2021) - Jadah, Raafat Hammad Seroor; Shaikho, Noor Mohamed Ghassan; Hasan, Sara Abdulla
Abstract : Epstein-Barr virus (EBV) infections are prevalent in the pediatric population but are subclinical in the majority of cases. Elevated transaminases in the acute setting rarely increase beyond 5 times the normal upper limit. We present a girl aged 1 y with fever, vomiting, and diarrhea. Although initial physical examination was unremarkable, she developed jaundice, hepatomegaly, abdominal distension, and a maculopapular rash during admission. Laboratory investigations revealed marked increase in transaminases (alanine aminotransferase 7, 664.5 IU/L, aspartate aminotransferase 12, 266 IU/L), elevated γ-glutamyl transferase (224 IU/L), and hyperbilirubinemia (total 130.7 µmol/L, direct 104.9 µmol/L). Abdominal ultrasound reported hepatomegaly with mild ascites. Serology revealed that both Monospot test and EBV immunoglobulin G were positive. With supportive therapy, improvement was noted within a week of symptom onset. We hereby elucidate the importance of considering EBV as a cause of acute cholestatic hepatitis in a very young pediatric patient who develops a rapid elevation of liver enzymes.